Color image encryption based on novel kolam scrambling and modified 2D logistic cascade map (2D LCM) - Mathivanan, P.; Maran, Ponnambalam (The Journal of supercomputing, 2024)
The proposed work combines existing one-dimensional chaos maps to create a new two-dimensional logistic cascade map (2D LCM) to produce better chaotic behavior. The system integrates novel kolam scrambling and a modified 2D LCM map to increase the security of the encryption process. The color image components of plaintext are permutated using the kolam scrambling method to remove adjacent pixel correlation during the confusion. Later, the modified 2D LCM map was used for key stream generation and encryption. Key space, entropy, correlation, NPCR, UACI and PSNR values for a single round of iteration are 2 449 , 7.99, − 0.0003, 33.4, 99.6, and 7.6451 dB, respectively. Furthermore, the scheme time complexity (TC) is O(6 × M × N ), with a total computation time of 1.54 s. Moreover, the resistance of the suggested method to key space, statistical attack, differential attack, and computation time is compared to that of existing standard chaos-based encryption algorithms, and it is determined to have good resistance and be appropriate for secure data transfer.